Transcriptome profiling of the theca interna in transition from small to large antral ovarian follicles. - Nicholas Hatzirodos; Katja Hummitzsch; Helen F Irving-Rodgers; Raymond J Rodgers (PLoS ONE, 2014)
The theca interna layer of the ovarian follicle forms during the antral stage of follicle development and lies adjacent to and directly outside the follicular basal lamina. It supplies androgens and communicates with the granulosa cells and the oocyte by extracellular signaling. To better understand developmental changes in the theca interna, we undertook transcriptome profiling of the theca interna from small (3-5 mm, n = 10) and large (9-12 mm, n = 5) healthy antral bovine follicles, representing a calculated >7-fold increase in the amount of thecal tissue. Principal Component Analysis and hierarchical classification of the signal intensity plots for the arrays showed no clustering of the theca interna samples into groups depending on follicle size or subcategories of small follicles. From the over 23,000 probe sets analysed, only 76 were differentially expressed between large and small healthy follicles. Some of the differentially expressed genes were associated with processes such as myoblast differentiation, protein ubiquitination, nitric oxide and transforming growth factor β signaling. The most significant pathway affected from our analyses was found to be Wnt signaling, which was suppressed in large follicles via down-regulation of WNT2B and up-regulation of the inhibitor FRZB. These changes in the transcriptional profile could have been due to changes in cellular function or alternatively since the theca interna is composed of a number of different cell types it could have been due to any systematic change in the volume density of any particular cell type. However, our study suggests that the transcriptional profile of the theca interna is relatively stable during antral follicle development unlike that of granulosa cells observed previously. Thus both the cellular composition and cellular behavior of the theca interna and its contribution to follicular development appear to be relatively constant throughout the follicle growth phase examined.